X-ray study of local infrared bright galaxies - Pereira-Santaella, M; Alonso-Herrero, A; Jiménez-Bailón, E; Rieke, GH; Santos-Lleo, M; Ward, M (Spanish Astronomical Society, 2010)
We are carrying out detailed study of the X-ray and infrared (IR) properties of a sample of local (d < 70 Mpc) luminous infrared galaxies (LIRGs) using XMM-Newton and Spitzer (imaging and spectroscopy). The main goal is to study the extreme processes of star formation and/or active galactic nuclei (AGN) taking place in this cosmologically important class of galaxies. In this proceedings we present the preliminary results obtained from the analysis of the XMM-Newton X-ray images and the X-ray spectral modeling.